The relationship between human capital development and economic growth: an Islamic analysis - Hashi, Abdurezak Abdulahi; Xareed, Bashir Abdisamad (2009)
Throughout its educational system and intellectual teachings, Islam provides certain themes and methods to improve human capacity of economic production and growth. Based on textual and analytical methods, this paper aims to expose horizons and methods of human capital development through which the Islamic perspective of the economic growth is presented, including sufficient knowledge and qualification (ilm and ahliyah) instilled with morality (akhlaq), work and production (amal), moralized consumption (infaq mutawazin), and justice (adalah). The Qur’anic dictums and the Prophetic statements related to the subject would be exposed, while the opinions of the Muslim jurists and expositors of the Qur’an on the subject would be unveiled